2016
DOI: 10.3892/ol.2016.4813
|View full text |Cite
|
Sign up to set email alerts
|

An observational study regarding the rate of growth in vertical and radial growth phase superficial spreading melanomas

Abstract: Abstract. The natural history of superficial spreading melanomas (SSMs) involves the progression from a radial growth phase (RGP) to a vertical growth phase (VGP). Currently, a patient's history represents the only method to estimate the rate of tumor growth. The present study aimed to verify whether the estimated rate of growth (ROG) of SSMs with a RGP or VGP exhibited any differences, and to evaluate the possible implications for the most important prognostic determinants. ROG was quantified as the ratio bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…As regards the first point, the present results support the prognostic impact of (mostly) well-established clinical-pathological variables ( 6 , 14 , 15 ). In particular, the Kaplan-Meier analysis showed that none of the RGP CMMs resulted in a melanoma-specific death within 5 years after the initial diagnosis ( 16 ). The present results also provide evidence to show that extra-nodal metastases from RGP CMMs are extremely rare (less than 3%), while almost all extra-nodal metastatic implants result from “vertically-growing” CMMs ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…As regards the first point, the present results support the prognostic impact of (mostly) well-established clinical-pathological variables ( 6 , 14 , 15 ). In particular, the Kaplan-Meier analysis showed that none of the RGP CMMs resulted in a melanoma-specific death within 5 years after the initial diagnosis ( 16 ). The present results also provide evidence to show that extra-nodal metastases from RGP CMMs are extremely rare (less than 3%), while almost all extra-nodal metastatic implants result from “vertically-growing” CMMs ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, melanoma represents a small portion (~1%) of annual skin cancer diagnoses but accounts for more than 65% of the deaths attributed to skin cancer (Cancer-Society, 2021 ; WHO-Cancer, 2021 ). As described in an observational study, the melanoma growth rate increases at a rate of 0.13 ± 0.16 mm/month (Betti et al, 2016 ). In turn, at depths greater than 0.3 mm, melanoma is at risk of metastasizing.…”
Section: Introductionmentioning
confidence: 85%
“…Screening is typically done with dermoscopy using a dermatoscope, which is a low-magnification, illuminated, polarized 5 contact imaging device widely used in dermatology practice. 6 A recent observational study 7 regarding the rate of growth in vertical and radial growth phase of superficially spreading melanomas found that melanomas in the vertical growth phase invade by . A delay in detection of a few months can negatively impact prognosis since growth beneath the -deep basal layer basement membrane constitutes invasion toward metastasis.…”
Section: Introductionmentioning
confidence: 99%